The Contribution of Women Empowerment on Family Relationships in Kauga, Mukono District - Tracy Namande (Uganda Christian University, 2025)
The study assesses the impact of women empowerment on family relationships, focusing on how increased agency, economic participation, education, and decision-making power among women influence dynamics within the household. As gender roles come up, empowered women contribute not only to the financial wellbeing of families but also to more equitable and cooperative domestic relationships. The research employs a mixed-method approach, combining quantitative surveys with qualitative interviews to capture the lived experiences of women across different socio-economic backgrounds. Findings indicate that women empowerment leads to improved communication, shared responsibilities, and enhanced emotional bonds within families. However, the study also highlights challenges, including resistance to shifting roles and the need for broader societal support. Overall, the research underscores that empowering women is not only a matter of individual rights but a catalyst for healthier, more resilient family structures.
Undergraduate